2013
DOI: 10.1162/rest_a_00288
|View full text |Cite
|
Sign up to set email alerts
|

Who Creates Jobs? Small versus Large versus Young

Abstract: Abstract-The view that small businesses create the most jobs remains appealing to policymakers and small business advocates. Using data from the Census Bureau's Business Dynamics Statistics and Longitudinal Business Database, we explore the many issues at the core of this ongoing debate. We find that the relationship between firm size and employment growth is sensitive to these issues. However, our main finding is that once we control for firm age, there is no systematic relationship between firm size and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

79
963
10
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,450 publications
(1,071 citation statements)
references
References 17 publications
(19 reference statements)
79
963
10
19
Order By: Relevance
“…The results show that the positive effect associated to the export status declines with firm age. Further, we also find that contrary to recent evidence on US (Haltiwanger et al, 2013) the negative size-growth relationship does not vanish even when accounting for the role of age. These results, which are robust to a series of controls, suggest a signaling role of the export status which is stronger for young exporters or born globals.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results show that the positive effect associated to the export status declines with firm age. Further, we also find that contrary to recent evidence on US (Haltiwanger et al, 2013) the negative size-growth relationship does not vanish even when accounting for the role of age. These results, which are robust to a series of controls, suggest a signaling role of the export status which is stronger for young exporters or born globals.…”
Section: Introductioncontrasting
confidence: 99%
“…Now, more recent contributions, that also look at the age of the firm, challenge that evidence. 2 In particular, Haltiwanger et al (2013), using data from the Census Bureau's Longitudinal Business Database (LBD), show that the negative relationship between firm size and growth disappears and may even reverse sign among the biggest firms. This evidence casts doubt on policy interventions aimed at small businesses but ignoring the role of firm age.…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurship is said to be a driving force of such structural change (Schumpeter 1934). Prior research has shown that ambitious entrepreneurship has stronger effects on economic growth than other types of entrepreneurship Wong et al 2005), and that young firms are a driver of job creation (Haltiwanger et al 2013;Criscuolo et al 2014), and that young high-growth firms accelerate the reallocation of jobs from old to new industries (Bos and Stam 2013). However, it may be the case that our -already very refined -measure of entrepreneurship does not sufficiently cover structural change, and is not an adequate indicator of emerging properties of the system.…”
Section: Structural Changementioning
confidence: 99%
“…Furthermore, there is evidence that HGFs, regardless of definition, are on average younger than other firms . A number of studies on firm growth argue that firm age is negatively associated with growth (Evans 1987;Dunne and Hughes 1999;Yasuda 2005;Calvo 2006;Haltiwanger et al 2013), and a link may exist at the industry level. We therefore expect that firms in industries with older firms are less likely to exhibit rapid firm growth, due to a lower level of business opportunity (e.g., Coad 2007: 40).…”
mentioning
confidence: 99%